Pengembangan dan Validasi Booklet Gizi Sebagai Upaya Peningkatan Pengetahuan Mengenai Fattening Foods pada Remaja - Firmansyah Firmansyah; Niken Damayanti; Nurhaya Kamilah; Agus Triyono; Meirina Dwi Larasati (Jurnal Kesehatan, 2023)
Introduction: The risk factors for non-communicable diseases such as obesity in adolescents are lifestyle changes that shift from traditional to western patterns, especially in diets high in saturated fat, sugar, fast food, and low in fiber. Knowledge of nutrition is still believed to be one of the factors that influence nutritional behavior. Objective: To determine the effect of nutrition booklets on knowledge and consumption of fattening foods among adolescents in Surakarta, Indonesia. Method: The type of research is Research and Development by developing nutrition booklets as media for nutrition education. The development of this media uses the ADDIE principle by carrying out the stages from development to implementation. The subjects of this study were media experts and material experts where each consisted of three people and became the media validators for the booklet to be compiled. Results: Based on the validation test of material experts, media experts, and targets, the fattening foods booklet media is included as a suitable medium with an average value of 4.2 while the CVI score shows a value of 1 which means the fattening foods booklet is relevant, the results of applying the fattening foods booklet media the average score of the pretest was 73 and the posttest was 95. Based on these data, it can be seen that there has been an increase in knowledge of fattening foods using the booklet as an aid of 30.1%. Conclusion: The fattening foods booklet media can be used as a means of information as an effort to increase knowledge of fattening foods in adolescents